Ein lokaler Grenzwertsatz für die Dichtefunktionen - Survila, P. (Lithuanian Mathematical Journal, 1964)
The abstracts (in two languages) can be found in the pdf file of the article.Original author name(s) and title in Russian and Lithuanian:П. Сурвила. Одна локальная предельная теорема для плотностейP. Survila. Viena ribinė lokalinė teorema tankiams